A Hierarchical Transcriptional Regulatory Network Required for Long-Term Thermal Stress Tolerance in an Industrial Saccharomyces cerevisiae Strain - Gan, Yuman; Qi, Xianni; Lin, Yuping; Guo, Yufeng; Zhang, Yuanyuan; Wang, Qinhong (Frontiers in Bioengineering and Biotechnology, 2022)
Yeast cells suffer from continuous and long-term thermal stress during high-temperature ethanol fermentation. Understanding the mechanism of yeast thermotolerance is important for not only studying microbial stress biology in basic research but also developing thermotolerant strains for industrial application. Here, we compared the effects of 23 transcription factor (TF) deletions on high-temperature ethanol fermentation and cell survivals after heat shock treatment, and identified three core TFs including Sin3, Srb2 and Mig1 that are involved in regulating the response to long-term thermotolerance. Further analyses of comparative transcriptome profiling of the core TF deletions and transcription regulatory associations revealed a hierarchical transcriptional regulatory network centered on these three TFs. This global transcriptional regulatory network provided a better understanding of the regulatory mechanism behind long-term thermal stress tolerance as well as potential targets for transcriptome engineering to improve the performance of high-temperature ethanol fermentation by industrial Saccharomyces cerevisiae strain.